Hierarchy and Its Discontents: Status Disagreement Leads to Withdrawal of Contribution and Lower Group Performance - Kilduff, Gavin J.; Willer, Robb; Anderson, Cameron (Organization Science, 2016)
Research on status and group productivity has highlighted that status hierarchies tend to emerge quickly and encourage contributions to group efforts by rewarding contributors with enhanced status. This and other status research has tended to assume that status hierarchies are agreed-upon among group members. Here, we build on recent work on status conflict in investigating the prevalence and consequences of situations in which group members hold differing perceptions of the status ordering—that is, of who ranks where—which we call status disagreement. Across two studies of interacting groups, we examined several different types of status disagreement and found that disagreements in which two group members both viewed themselves as higher in status than the other, or upward disagreements, were uniquely harmful for groups. These types of disagreements led the involved members to reduce their contributions to the group, substantially decreasing group performance. However, other forms of dyadic status disagreements, as well as overall levels of status consensus, did not significantly affect group functioning. Furthermore, we found that individuals higher in personality dominance were those most likely to be involved in these harmful upward disagreements. These findings demonstrate the importance of more thoroughly considering status disagreement as a dimension that can vary in quantity and type across groups. In doing so, they contribute to understanding of status dynamics and group performance and suggest important implications for teams within organizations.